Aplikasi Peringkas Teks Bahasa Indonesia Menggunakan Model Text-to-Text Transfer Transformer (T5) - Yani, Mohammad; Khodijah, Nur Siti; Rendi; Mustamiin, Muhamad (Fakultas Teknik Universitas Persada Indonesia YAI, 2025)
In the digital era, information can be easily accessed through various available media suchas search engines, academic repositories, social media, news portals, and websites.However, the information available is often presented in lengthy textual form. For instance,information about 'Joko Widodo' on the Wikipedia page contains at least 8,716 charactersof text. Such a long text can be challenging to extract its main points efficiently. Severalstudies have been conducted on the development of text summarization applications.Nevertheless, a summarization application that accepts input from various formats has notyet been developed. In this research, the author proposes a text summarization systemcapable of summarizing text using inputs in multiple formats. This text summarizationsystem processes information inputs in the form of text, document files, web pages, andimages, which are subsequently summarized using the Text-to-Text Transfer Transformer(T5) model to generate a summarized output that can be stored in various file formats.Evaluation results indicate that text summarization with document or text file inputs yieldshigher ROUGE scores compared to non-text inputs, reaching an average score of 0.87